2012
DOI: 10.3184/095422912x13255245250543
|View full text |Cite
|
Sign up to set email alerts
|

Chemical forms of heavy metals in soils around municipal waste dumpsites in Asaba Metropolis, Delta State, Nigeria

Abstract: The chemical forms of copper, lead, manganese and zinc in soils around five selected municipal waste dumpsites in Asaba metropolis, Delta State, Nigeria, were studied, using the Ma and Rao six-step sequential chemical extraction procedure, with a view to providing information on the bioavailability and mobility of the metals in the soil matrix. The results showed that lead and manganese were speciated into residual fractions with averages of 60.32 and 82.24% respectively, while copper and zinc were associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
(54 reference statements)
1
16
2
Order By: Relevance
“…This result is in agreement with those reported by Helali et al, (2013); Woszczyk and Spychalsk (2013), Ogubanjo et al, (2016). The proportion of organic matter associated with lead obtained in this study is higher than those reported by Osakwe et al, (2012), Ibrahim et al, (2013) but lower than those reported by Asagba et al,(2007), Li and Thornton (2001). LopezSanchezet al,(1996) suggested that lead is usually associated with organic fraction because it forms stable complex with the organic matter.…”
Section: Leadcontrasting
confidence: 59%
See 2 more Smart Citations
“…This result is in agreement with those reported by Helali et al, (2013); Woszczyk and Spychalsk (2013), Ogubanjo et al, (2016). The proportion of organic matter associated with lead obtained in this study is higher than those reported by Osakwe et al, (2012), Ibrahim et al, (2013) but lower than those reported by Asagba et al,(2007), Li and Thornton (2001). LopezSanchezet al,(1996) suggested that lead is usually associated with organic fraction because it forms stable complex with the organic matter.…”
Section: Leadcontrasting
confidence: 59%
“…Asagba et al, (2007) reported an average of 25.8% while Osakwe et al(2012) and Kumar et al (2014) reported 10.88% and 9.50% of copper contents respectively in this phase. Studies have shown that this fraction sequestrates metals in the environment (Nachtegaal andSparks, 2004, Asagba et al, 2007).…”
Section: Coppermentioning
confidence: 87%
See 1 more Smart Citation
“…There is an increasing concern regarding food safety due to environmental pollution (Ma and Rao, 1997;Li andThornton, 2001;Yang et al, 2009), in which soil pollution with anthropogenic heavy metals released from industry or agriculture such as smelting industries, residues from metalliferous mines, pesticides, fertilisers, municipal composts, has received much attention in recent years (Lu et al, 2005;Liu et at., 2007a;Guo et al, 2008Wu et al, 2010;Chen et al, 2011;Wang et al, 2012;Guo et al, 2012;Osakwe et al, 2012;Shao et al, 2013;Xu et al, 2013). Heavy metals in soils cannot be biodegraded, but can be bioaccumulated and bio-transformed by plants, and pose toxicity to plants beyond certain limits (Nan and Zhao, 2000;Nan and Cheng, 2001;Nan et al, 2002;Ding et al, 2008;Nan et al, 2011;Yang et al, 2011aYang et al, , 2011bWang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the previous results (Li and Thornton, 2001;Chaudhary and Banerjee, 2004;Ogundiran and Osibanjo, 2009;Luo et al, 2012b) Cd and Pb are known to be preferentially associated with carbonate minerals, due to their similar size to the Ca ion (Rimstidt et al, 1998), thus a substantial proportion of Cd and Pb in various soils is usually associated with carbonates in the soils (Han and Banin, 1997;Maskall and Thornton, 1997;Faiga et al, 2011;Hu et al, 2011). On the other hand, soil organic matter fixes Cu very strongly (Bloom, 1981), thus a substantial proportion of Cu in various soils is often associated with soil organic matter (Han and Banin, 1997;Mehra et al, 1999;Lin et al, 2008b;Osakwe et al, 2012). In the urban soils in Nanjing (China), about 92.9% of Cr and 60.0% of Zn were associated with RES fractions (Lu et al, 2003), similar to the results found in this study.…”
Section: Chemical Forms Of Heavy Metals In the Soilmentioning
confidence: 99%